Gurdwara politics vs comumuity development: Malaysian case. - Sarjit , S. Gill (2007)
This paper focuses on the Gurdwara (Sikh religious institution) and its politics, which is currently of considerable importance in the formation of Sikh identity in Malaysia. All Sikh functions, collective as well as individual,are generally performed in local Gurdwaras. The Gurdwara plays an essential role in developing the Sikh community. As Sikhism is a faith which recognises no division between religion and politics, all major political Sikh movements in the Punjab have sprung from Gurdwaras. In Malaysia, each Sikh religious organisation or Gurdwara enjoys an independent administration. Hence, Gurdwaras Management Committee (GMC) members who run the Gurdwara administration are 'respected' by the Sikh community. In 1988, a central council of Gurdwaras called the Malaysian Gurdwaras Council (MGC) was established to coordinate the functioning of these Gurdwaras. Based on onr research, we found that, most of the Malaysian Gurdwaras are facing similar challenges. The ideal roles of the Granthi Sahib as a religions specialist are in question. The Granthi Sahib and GMC are iu a dilemma about their roles, The reason for this conflict will be explored in this paper. It needs to be mentioned that there are conflicts between the GMC and Granthi Sahib dne to committee member influences and their abuse of power in their relations with religions specialists, who are the minority group in the Sikh community. Therefore, the nature of role of the MGC in addressing theSe tensions which in turn affect the formation of Sikh identity will be discussed in detail.